Insufficient declines in new HIV infection rates amidst high scores in HIV testing and awareness: ‘a game theory simulation’ - Ochanda, Perez Nicholas; Ssempala, Richard; Kayongo, Allan; Odokonyero, Tonny (Journal of public health, 2022)
Aim Substantial progress has been made towards the 90–90–90 global targets; however, the pace at which new infections are declining remains undesirable to meet the UNAIDS 2020 global targets of below 500,000 new infections annually. We discussed the possibility of continued HIV incidence amidst remarkable scores in the 90–90–90 global targets. Subject and methods A game theory simulation was used to explain micro-level sexual interactions in situations of imperfect information on each partner’s HIV status. A non-cooperative sex game tree was constructed following the Harsanyi transformation in two scenarios; scenario one: a player assigns higher subjective probability that the partner is HIV negative; and in scenario two: a player assigns higher subjective probability that the partner is HIV positive. Subjective expected utilities were computed using hypothetical payoffs. Results Accepting unprotected sex is a pure strategy for both players in scenario 1. Player2 is likely to acquire HIV/AIDS. Accepting protected sex is a mixed strategy equilibrium for both players in scenario 2. Player2 is likely to avoid HIV infection. Conclusion Choice for safe or risky sex is a function of subjective probabilities individuals attach to their partners being infected or uninfected. More efforts towards addressing factors affecting individual probability distributions on riskiness of their sexual partners is required, especially for young women in Sub-Saharan Africa.